Computational modeling suggests distinct, location-specific function of norepinephrine in olfactory bulb and piriform cortex - de Almeida, Licurgo; Reiner, Seungdo J.; Ennis, Matthew; Linster, Christiane (Frontiers in Computational Neuroscience, 2015)
Noradrenergic modulation from the locus coerulus is often associated with the regulation of sensory signal-to-noise ratio. In the olfactory system, noradrenergic modulation affects both bulbar and cortical processing, and has been show to modulate the detection of low concentration stimuli. We here implemented a computational model of the olfactory bulb and piriform cortex, based on known experimental results, to explore how noradrenergic modulation in the olfactory bulb and piriform cortex interact to regulate odor processing. We show that as predicted by behavioral experiments in our lab, norepinephrine can play a critical role in modulating the detection and associative learning of very low odor concentrations. Our simulations show that bulbar norepinephrine serves to pre-process odor representations to facilitate cortical learning, but not recall. We observe the typical non-uniform dose – response functions described for norepinephrine modulation and show that these are imposed mainly by bulbar, but not cortical processing.